Membangkitkan Realitas Alternatif: Konsep “Imajinasi Profetik” Walter Brueggemann sebagai Metafora Kitab Suci bagi Kontestasi Naratif Realitas Kontemporer - Nathaniel Hendradi (Indonesian Journal of Theology, 2022)
Modern scholars of narrative, such as Ninian Smart, Paul G. Hiebert, Charles Taylor, James W. Sire, and James K.A. Smith, affirm the centrality of narrative for shaping the identity and spirituality of individuals and society. The power of narrative attends the dimension of the imaginal, which is manifest in mythical stories. Such scholarship draws primarily upon sociological/anthropological approaches if not, more simply, a humanities-oriented disciplinarity. While maintaining an appreciation for such precedent studies, this article aims to make a discursive contribution to the subject at hand—a contribution that considers the discourse on narrative and mythical stories from biblical studies perspective, given the significance of what it means to perceive the human person in complex and holistic fashion. The author holds the centrality of the scriptural text for determining the life and faith of God’s people, given that the text comprises God’s narrative: as foundation, as memory, and as their mythical framework. Utilizing Walter Brueggemann’s notion of the “prophetic imagination,” this article proposes that the metaphor of Scripture serves as a model for encountering the reality of contemporary life, surrounded as each one is by narrative contestations.